Globalization, Self-Determination and Violent Conflict
IX, 270 p.
Keywords: The authors show that with violent conflict in the developing world as the critical issue for the twenty-first century, and conflict prevention a central security problem for the developed and developing world, self-determination movements can only be understood, and conflict prevented, in the context of global economic and cultural forces.